Students’ Strategies with Technology Integrated to Overcome the Interlanguage Issue - Fitriani, Naria; Anhar, Anhar; Sabarniati, Sabarniati (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2024)
During the achievement of the target language, interlanguage becomes a serious issue in second language acquisition (SLA). The influence of the student’s mother tongue both on vocabulary and structure plays an essential role, particularly in oral performance. This qualitative study aims to find out the interlanguage fossilization as well as the digital media used to overcome the interlanguage. In this study, 23 non-English department students participated by videotaping their speaking performance spontaneously for about two minutes. Each student submitted a video on the subject of “My Childhood” via google classroom at the end of the English program. Not only the documentation but also the interview is employed; five of the students took part in it. Additionally, the students’ strategies to be proficient in English were expressed. The findings indicated the syntactical errors in pronouns errors, articles, concords, and fragments and the morpheme errors in suffixes. Meanwhile, learning English videos integrated with technology such as YouTube, TikTok, and Instagram promotes the students’ strategies to boost their speaking skills.